Taxonomical and biological notes on Neotropical Apiomerini (Hemiptera: Heteroptera: Reduviidae: Harpactorinae) - Gil-Santana, Hélcio R.; Forero, Dimitri (Zootaxa, 2010)
New occurrences of Apiomerini species are recorded: Apiomerus arnaui Costa Lima, Seabra & Hathaway and Apiomerus gallegoi Costa Lima, Seabra & Hathaway from Brazil, and Heniartes scutellatus Wygodzinsky from Surinam. Remarks on the color variation of Agriocleptes bahianus Wygodzinsky, Apiomerus evanidus Distant, Apiomerus gallegoi, and Heniartes scutellatus are given. Based on color variation within a single population and the absence of structural differences between the two forms, Heniartes australis Wygodzinsky is placed in synonymy with Heniartes jaakkoi Wygodzinsky. Observations on sticky substances on fore legs of live nymphal instars of Apiomerus mutabilis and Heniartes jaakkoi are provided. Occurrence of eggs of Tachinidae on adults of Heniartes jaakkoi and Apiomerus mutabilis Costa Lima, Seabra & Hathaway is recorded for the first time for the tribe Apiomerini.